Candidate genes potentially involved in molting and body size reduction in the male of the horned gall aphid, Schlechtendalia chinensis - Wei, Hongyuan; Xu, Xin; Feng, Guorui; Shao, Shuxia; Chen, Xiaoming; Yang, Zixiang (Frontiers in Physiology, 2023)
In general, insects grow (increase in body size) through molting. To the opposite, the body size of the males of the horned gall aphid, Schlechtendalia chinensis, gets smaller after molting and as they age. To understand the molecular bases of this rare phenomenon, transcriptomes were generated from 1-5 days old male and the data were analyzed via a weighted gene co-expression network analysis (WGCNA). A total of 15 partitioned modules with different topological overlaps were obtained, and four modules were identified as highly significant for male body length (p<0.05). KEGG enrichment analysis suggested that a portion of genes in the four modules are likely involved in autophagy and apoptosis. In addition, a total of 40 hub genes were obtained in the four modules, and among them eight genes were highly expressed in males compared to individuals of other generations of S. chinensis. These eight genes were associated with autophagy and apoptosis. Our results reveal the unique negative growth phenomenon in male S. chinensis after molting, and also suggest that the male S. chinensis with no ability to feed probably decompose their own substances via autophagy and apoptosis to provide energy for life activities such as germ cell development.